Development Of Human Resources For Islamic Education - Sakban Sakban; Wahyu Khafidah (Ruhama : Islamic Education Journal, 2021)
Generalization of education as generalization of opportunity to obtain;get to education, education have role expand education democratization it with password of education all for. Generalization of education include;cover two important aspect that is and equality of equity. Equality or meaningful equation of equation of opportunity to obtain;get to education, while equity have a meaning (of) justice in getting the opportunity is same education among various group in society. Access to education which flatten to mean all school age resident have got the opportunity education, meanwhile access to education have fair if between group can enjoy education is samely.